2006
DOI: 10.1016/j.jconhyd.2006.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution kinetics of high explosives particles in a saturated sandy soil

Abstract: Solid phase high explosive (HE) residues from munitions detonation may be a persistent source of soil and groundwater contamination at military training ranges. Saturated soil column tests were conducted to observe the dissolution behavior of individual components (RDX, HMX, and TNT) from two HE formulations (Comp B and C4). HE particles dissolved readily, with higher velocities yielding higher dissolution rates, higher mass transfer coefficients, and lower effluent concentrations. Effluent concentrations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 12 publications
(32 reference statements)
3
26
0
Order By: Relevance
“…They more closely simulate the physical circumstances of HE particles exposed to rainfall on surface soils than do stirred-bath (Lynch et al, 2002a,b) or glass-bead column experiments (Phelan et al, 2003). They yield estimates of aqueous HE influx to surface soils as functions of particle size, particle composition and rainfall rate while avoiding the complexity of aqueous-phase HE-soil interactions that occur during soil-column experiments Morley et al, 2006). TNT and RDX mass recoveries from all particles were very good; HMX mass recovery was complicated by its low-solubility and disaggregation of the Octol particles following complete TNT dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…They more closely simulate the physical circumstances of HE particles exposed to rainfall on surface soils than do stirred-bath (Lynch et al, 2002a,b) or glass-bead column experiments (Phelan et al, 2003). They yield estimates of aqueous HE influx to surface soils as functions of particle size, particle composition and rainfall rate while avoiding the complexity of aqueous-phase HE-soil interactions that occur during soil-column experiments Morley et al, 2006). TNT and RDX mass recoveries from all particles were very good; HMX mass recovery was complicated by its low-solubility and disaggregation of the Octol particles following complete TNT dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to its use by the Canadian Army, the new GIM formulation should therefore be tested for its potential impact on the environment. Dissolution of explosives by precipitation is the departure point and one of the controlling factors for the transport, fate, and impact of explosives [8,9]. Moreover, few studies suggested that the dissolution rate of individual explosives was decreased when present in formulations compared to the pure explosives [10][11][12][13].…”
Section: E-mail Addressmentioning
confidence: 99%
“…The explosive contamination in soil and groundwater is usually caused by the dissolution of 0304-3894/$ -see front matter © 2012 Elsevier B.V. All rights reserved. http://dx.doi.org/10.1016/j.jhazmat.2012.07.035 different types of solid-phase energetic residues [1,[4][5][6][7][8][9][10], such as the widely used TNT, Tritonal (TNT/aluminum: 80/20), Composition B (RDX/TNT/wax: 60/39/1), and Octol (HMX/TNT: 70/30) [6], and the recently developed GIM [HMX/TNT/ETPE (energetic thermoplastic elastomer): 51/41/8] [11]. Apart from the TNT, the other mentioned high-energy explosives are all melt cast, where aluminum, RDX, and/or HMX crystals together with some binding materials are added into the molten TNT for subsequent solidification [6].…”
Section: Introductionmentioning
confidence: 99%
“…Because dissolution is usually the primary mechanism and the first step controlling the entry and spreading of explosive compounds into subsurface environments [1,[4][5][6][7][8][9][10]12], dissolution of either individual compounds, e.g. the pure crystals of TNT, RDX, and HMX, or their mixed residues, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation